PELAYANAN KESEHATAN KOMPREHENSIF BAGI PEKERJA WISATA YANG DIRUMAHKAN SEJAK PANDEMI COVID-19 - Yanti, N.P E.D.; Krisnawati, K.M. S.; Suarningsih, K. A.; Utami, K. C. (Buletin Udayana Mengabdi, 2022)
Corona Virus Diseases 2019 (COVID-19) pandemic has caused many tourism workers in Bali to be laid off. This certainly affects the physical and psychological health of the laid-off employees. Employees who are laid off can experience stress. The purpose of this community service is to reduce the stress level of tourist workers who have been laid off since the COVID-19 pandemic in Paksebali Village, Klungkung after being given health education and doing self-hypnosis. This community service is carried out in the form of health services including stress level screening using Depression Anxiety Stress Scales and health education on how to manage stress with self-hypnosis. Lecture, discussion, and simulation methods used in the implementation of health education with a duration of 180 minutes and attended by 70 participants. An online questionnaire was used to collect data describing the stress level of the participants. The description of the stress level of participants before being given treatment was found to be 70% in the normal category. The health education activities went smoothly, the participants seemed to be actively listening, asking questions, answering questions, and participating in the simulations given by the resource persons. Health counseling using lecture, discussion, and simulation methods about managing stress with self-hypnosis is expected to increase participants' knowledge and positive behavior in managing stress during the Covid-19 pandemic.   Keywords: Health Education, Pandemic, Self-hypnosis, Travel Workers